Energy harvesting from car suspension system: Mathematical approach for half car model - Tariq Darabseh; Doaa Al-Yafeai; Abdel-Hamid Ismail Mourad (Journal of Mechanical Engineering and Sciences, 2021)
A significant contribution of this paper is developing a half car model with a built-in piezoelectric stack to evaluate the potential of harvesting power from the car suspension system. The regenerative car suspension system is modelled mathematically using Laplace transformation and simulated using MATLAB/Simulink. Two piezoelectric stacks are installed in series with the front and rear suspension springs to maintain the performance of the original suspension system in ride quality and comfortability. Half car model is subjected under harmonic excitation with acceleration of 0.5 g and velocity of 9.17 rad/s. The harvested voltage and power are tested in both time, and frequency domain approaches. The influence of the different parameters of the piezoelectric stack (number of stack layers and area to thickness) and car suspension (sprung and unsprung stiffness and damping coefficients) are examined. Also, the effect of road amplitude unevenness is considered. The results illustrate that the maximum generated voltage and power at the excitation frequency of 1.46 Hz are 33.51 V and 56.25 mW, respectively.